Acute and Chronic Effects of High-Load Resistance Training With Blood Flow Restriction in Healthy Adults: A Systematic Review and Meta-Analysis. - Mckee, James R.; Selva Raj, Isaac; Marston, Kieran J.; De Marco, Kristen; Beere, Michael; Galna, Brook; Peiffer, Jeremiah J.; Nosaka, Kazunori; Scott, Brendan R. (Journal of Strength & Conditioning Research, 2026)
Supplemental Digital Content Is Available in the Text. Mckee, JR, Raj, IS, Marston, KJ, De Marco, K, Beere, M, Galna, B, Peiffer, JJ, Nosaka, K, and Scott, BR. Acute and chronic effects of high-load resistance training with blood flow restriction in healthy adults: A systematic review and meta-analysis. J Strength Cond Res 40(7): 822–842, 2026—Blood flow restriction (BFR) improves muscle strength and size gains after low-load resistance training, though findings are conflicting for BFR with higher loads (≥60% of maximal strength). This systematic review with meta-analysis investigated whether high-load resistance training with BFR (a) further improves muscle size and strength and (b) increases acute performance, physiologic, and perceptual responses, when compared with conventional high-load resistance training. Six databases were searched to identify studies examining high-load resistance training with BFR in healthy adults. Risk of bias was assessed using Joanna Briggs Institute appraisal tools. A multilevel meta-analysis using the inverse-variance weighted random effects model was conducted on muscle strength and size outcomes. Acute data were synthesized narratively. Eight chronic studies and 34 acute studies were included. Very-low certainty evidence indicates that high-load resistance training with BFR does not further improve muscle strength (g = 0.11 [95% confidence intervals −0.11 to 0.33]) or size (g = 0.08 [95% confidence intervals −0.18 to 0.34]) adaptations compared with conventional high-load resistance training. Acutely, high-load resistance exercise with BFR may increase concentric bar velocity without altering electromyography amplitude, cardiorespiratory, metabolic, and molecular responses. Findings regarding perceptual responses and the number of repetitions completed during high-load resistance exercise with BFR are conflicting. Current evidence suggests that adding BFR to high-load resistance training is not beneficial for enhancing muscle size and strength, likely because of comparable physiologic demands. However, the application of wide cuffs at high pressures may acutely increase concentric bar velocity that could be explored as a potential method for improving muscular power.